2015
DOI: 10.18632/oncotarget.3801
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic analysis reveals exosomes are more oncogenic than ectosomes

Abstract: Extracellular vesicles (EVs) include the exosomes (30-100 nm) that are produced through the endocytic pathway via the multivesicular bodies and the ectosomes (100-1000 nm) that are released through the budding of the plasma membrane. Despite the differences in the mode of biogenesis and size, reliable markers that can distinguish between exosomes and ectosomes are non-existent. Moreover, the precise functional differences between exosomes and ectosomes remains poorly characterised. Here, using label-free quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
210
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(228 citation statements)
references
References 59 publications
17
210
1
Order By: Relevance
“…Comparing the molecular signatures of tumor- (26)(27)(28)(29) and DC-derived (our work) medium EVs will surely provide additional specific markers. So far, we have not identified a protein that would be exclusively in medium EVs, and not also in the largest ones, which the other groups working on tumorderived EVs did not evaluate: although it would be very useful, finding a specific marker for these particular EVs may be challenging.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Comparing the molecular signatures of tumor- (26)(27)(28)(29) and DC-derived (our work) medium EVs will surely provide additional specific markers. So far, we have not identified a protein that would be exclusively in medium EVs, and not also in the largest ones, which the other groups working on tumorderived EVs did not evaluate: although it would be very useful, finding a specific marker for these particular EVs may be challenging.…”
Section: Discussionmentioning
confidence: 86%
“…To obtain these results, it was necessary to combine several separation procedures and to follow a nonbiased approach, rather than a molecule-or EV subtype-targeted one. Some groups have recently performed comparative proteomic analyses of medium-sized and small EVs (with or without floatation into a gradient) from platelets (19) or tumor cells (26)(27)(28)(29). Another group has compared the expression of a few surface proteins on B lymphoma-EVs immunoprecipitated with either CD9, CD63, or CD81 (30).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of integrins on exosomes has previously been reported (6,49). Exosome-associated integrins are important in cancer metastasis and preferential exosome uptake by specific cells (12).…”
Section: Discussionmentioning
confidence: 94%
“…EVs, encompassing subcategories such as exosomes, microvesicles and apoptotic bodies, constitute structures secreted from cells and are surrounded by a phospholipid bilayer membrane whose constituents may reflect their cells of origin (2,3). It has been demonstrated that the content of exosomes may be selectively incorporated (4,5), with examples of oncogenic proteins enriched in exosomes compared with their cells of origin (6). The largest of the EVs are apoptotic bodies and microvesicles, both originating from the plasma membrane (7), whereas smaller EVs, so called exosomes, are formed intracellularly by multiple invaginations of the late endocytic membrane, leading to formation of vesicle-containing endosomes called multivesicular bodies (8,9).…”
mentioning
confidence: 99%
“…Proteomics studies, however, have discovered a growing set of GPCR family proteins, including GPR179 (14), GPR155 (15), GPR100 (16), and GPRC5 family proteins (17), that are cargos of extracellular vesicles. This suggests that GPCR family proteins may also mediate intercellular communications when transported to target cells via extracellular vesicles.…”
mentioning
confidence: 99%